2019
DOI: 10.1186/s41240-019-0122-7
|View full text |Cite
|
Sign up to set email alerts
|

Hexane fraction from the ethanolic extract of Sargassum serratifolium suppresses cell adhesion molecules via regulation of NF-κB and Nrf2 pathway in human umbilical vein endothelial cells

Abstract: Sargassum serratifolium ethanolic extract has been known for strong antioxidant and anti-inflammatory properties. We prepared hexane fraction from the ethanolic extract of S. serratifolium (HSS) to improve biological activities. In this study, we investigated the effects of HSS on the inhibition of tumor necrosis factor (TNF)-α-induced monocyte adhesion to human umbilical vein endothelial cells (HUVECs). We found that HSS suppressed the production of cell adhesion molecules such as intracellular adhesion molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…These facts indicated that the relatively lipophilic compounds tended to be responsible for the anti-inflammatory activity. This was supported by several other studies showing a similar tendency that a relatively lipophylic extract or fraction has a promising anti-inflammatory effect [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33].…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentssupporting
confidence: 75%
See 2 more Smart Citations
“…These facts indicated that the relatively lipophilic compounds tended to be responsible for the anti-inflammatory activity. This was supported by several other studies showing a similar tendency that a relatively lipophylic extract or fraction has a promising anti-inflammatory effect [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33].…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentssupporting
confidence: 75%
“…wightii were effective in inhibiting the COX-2 enzyme activity. Several other compounds that are allegedly responsible for the anti-inflammatory activity of the non-polar fraction include fucoxanthin or its derivatives [33], fucosterol or other steroid compounds [20,23,28,29,31,33,51], and phenolic compounds [18,23,30,31,33]. Although phenolic compounds are commonly known to have hydrophilic natures, their polarities will actually depend on their chemical structures.…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the specimen was confirmed by algal taxonomist C. G. Choi, who is affiliated with the Department of Ecological Engineering at Pukyong National University, Republic of Korea. Subsequently, a voucher specimen (TC18835) was deposited in the Marine Brown Algae Resources Bank, Republic of Korea [41]. The purity of the isolated sargachromenol exceeded 98 %, as assessed by an HPLC system equipped with a Luna RP-18 column (Luna C18(2), 3 µm, 150 × 3.0 mm) [15].…”
Section: Isolation Of Sargachromenol From S Serratifoliummentioning
confidence: 99%
“…Several studies on Sargassum summarized by Saraswati et al [ 6 ] indicated the promising anti-inflammatory effect of this seaweed genus, for both acute and chronic conditions. Although several screening studies demonstrated the predominance of Sargassum lipid-soluble fractions which are responsible for inflammatory activity [ 7 , 8 , 9 , 10 ], the potency of the lipid-soluble compounds of tropical Sargassum has not been fully explored. To date of our knowledge, the sulfated polysaccharides of tropical Sargassum are the most studied compounds for their anti-inflammatory activity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%